CuO nanowires fabricated by thermal oxidation of Cu foils towards electrochemical detection of glucose - Cao, Xun (2023)
In view of the various stability issues and high cost of enzymatic glucose biosensors, non-enzymatic biosensors have received great attention in recent research and development. Copper oxide (CuO) nanowires (NWs) were fabricated on Cu foil substrate using a simple thermal oxidation method. The phase and morphology of the CuO NWs could be controlled by synthesis temperature. Variation in oxidation states enables CuO NWs to form Cu (III) species, which is crucial in catalysing the eletro-oxidation of glucose. The Cu-based metal/oxide composite electrode works as a non-enzymatic biosensor that adapts to the fast, dynamic change in glucose concentration, with a low saturation concentration (~0.7 mM) and a lower detection limit of 0.1 mM, making CuO NWs an excellent sensor towards impaired fasting glucose. The simplicity, cost-effectiveness and non-toxicity features of this study might make a way for potentially scalable application in glucose biosensing.